STUDENTS’ ERROR IN USING PERSONAL PRONOUNS IN WRITING NARRATIVE TEXT AT TENTH GRADE OF SMAN 01 RAMBAH SAMO - Wahyuni; Rivi Antoni (English Study Program University of Pasir Pengaraian, 2019)
The purpose of this research was to find out the types of students’ error in using personal pronouns in writing narrative text. The indicators are: (1) Omission, (2) Addition, (3) Selection, (4) Ordering. By those indicators, the researcher would know the kinds of error that made by the students in using personal pronouns in writing narrative text. This was a qualitative descriptive study. The population was tenth grade students of SMAN 1 Rambah Samo. The samples were 29 student, that taken by using random sampling technique. The instrument was writing test. From the finding of the study, it can be seen in the high frequency error was made by students was error of selection with 75 errors, which means 60 % of error total. The next most error made by the students was error of ordering with 23 errors or 19 %. The students made 20 errors of error of omission or 16 %. They also made 6 errors of addition or 5 %. As a result, it can be concluded that the students still have problem in using personal pronouns in writing narrative text.